Arctic Art & Culture - Ignatieva, S.; Kharlampieva, N.; Dyakonova, V. (The Federal State-Funded Educational Institution of Higher Education, 2023)
The popular science review includes the materials about educational, research, scientific and practical activity of the team from the Arctic State Institute of Culture and Arts, their partners, and the Northern Forum regions facilitating the modern image-making of the North and Arctic.